Integration of Islamic Law into Local Governance: the Impact of Datuk Tellue’s Da’wah in South Sulawesi - Muh Yusuf (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2024)
The Islamization of South Sulawesi, particularly in the Bugis-Makassar hinterland, represents a significant shift in Indonesia's religious and socio-political history. This article highlights the migration of Islamic scholars from West Sumatra to key kingdoms in the region, which contributed to the formation of new Islamic landscapes that were previously recognized only in localized contexts. The integration of Islamic teachings into local governance systems, particularly through Pangngaderreng, succeeded in establishing Islam not only as a religion but also as a foundation for state legislation. This paper examines the da’wah strategies employed by Datuk Tellue, including (1) da’wah bi al-Hal, (2) da’wah bi al-Lisan, and (3) da’wah bi al-Aqd, and their impact on cultural and political dynamics in South Sulawesi. The study reveals how Islam was interwoven with local traditions and governance structures to shape a unique Islamic identity in the region. Furthermore, the establishment of Islamic educational institutions and councils such as Parewa Sara played a critical role in ensuring the continued influence of Islam in South Sulawesi.